2012
DOI: 10.1097/mpg.0b013e31822ecaac
|View full text |Cite
|
Sign up to set email alerts
|

Time‐series Analysis of Ondansetron Use in Pediatric Gastroenteritis

Abstract: Ondansetron use has increased significantly and is associated with reductions in the use of intravenous rehydration, emergency department revisits, and length of stay. The selective use of ondansetron is associated with improved clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 26 publications
0
16
1
3
Order By: Relevance
“…This would ensure adequate variation in ondansetron use and enable the establishment of a lag period, which facilitates the detection of a change in outcomes in timeseries designs. 10 Hospitalization was defined as admission to an observation (ie, short stay, 24 hours) or inpatient unit. For revisit outcomes, a 3-day window, generally accepted as an ED quality of care metric, 21 23 were used to assess the associations, at the hospital level, of ondansetron use category with the primary and secondary outcomes adjusting for potential confounding by observed baseline characteristics identified in bivariate analysis (ie, age, sex, race, season, admission time, prior visit for AGE, laboratory testing, diagnostic imaging, and rotavirus diagnosis), including quadratic terms when significant.…”
Section: Study Definitions and Participant Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…This would ensure adequate variation in ondansetron use and enable the establishment of a lag period, which facilitates the detection of a change in outcomes in timeseries designs. 10 Hospitalization was defined as admission to an observation (ie, short stay, 24 hours) or inpatient unit. For revisit outcomes, a 3-day window, generally accepted as an ED quality of care metric, 21 23 were used to assess the associations, at the hospital level, of ondansetron use category with the primary and secondary outcomes adjusting for potential confounding by observed baseline characteristics identified in bivariate analysis (ie, age, sex, race, season, admission time, prior visit for AGE, laboratory testing, diagnostic imaging, and rotavirus diagnosis), including quadratic terms when significant.…”
Section: Study Definitions and Participant Characteristicsmentioning
confidence: 99%
“…[8][9][10] Studies have demonstrated efficacy of ondansetron in children with mild to moderate dehydration who had initially failed ORT 9,11 and in those with multiple episodes of vomiting prior to ED presentation. 12 Although now administered to more than 50% of children with AGE in US EDs, 13 its administration is not recommended in guidelines endorsed by the American Academy of Pediatrics.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Este cambio se ha debido a ensayos clínicos dónde se demostró resolución del estado nauseoso y una adecuada recuperación de su equilibrio hidroelectrolítico. [4][5][6] Asimismo, su administración no provocó efectos secundarios serios y redujo el costo de atención. [4][5][6] De los antieméticos probados el más estudiado ha sido el ondansetrón, 4 con el cual se ha reducido tanto la rehidratación endovenosa de 31% a 14% como la hospitalización de 97% a 25%, así como el tiempo de estancia intrahospitalaria a menos de un día.…”
Section: Wwwmedigraphicorgmxunclassified
“…As ondansetron use gradually increased in period 2, this period was considered an "intersection" segment, and such children were excluded from this portion of the analysis. 26 To assess consistency of data abstraction, 10% of charts were identified at random, using a random number generator (Microsoft Office Excel 2007, Redmond, Washington), and reviewed in a blinded fashion by a second reviewer (M.R. or J.L.).…”
Section: Statistical Analysesmentioning
confidence: 99%